Cyberloafing and Organizational Citizenship Behavior as Correlates of Performance: Towards an Enhanced Evaluation Tool - Ortiz, Ma. Arjean L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study examines the interplay between cyberloafing, Or-ganizational Citizenship Behavior (OCB), and employee perfor-mance. Cyberloafing, defined as personal use of company internet during work hours, and OCB, comprising voluntary behaviors that enhance organizational effectiveness, are analyzed as predictors of job performance. The research aims to develop an Enhanced Productivity Evaluation Tool (EPET) to assess the impact of these behaviors on performance outcomes.Using a quantitative approach, data were collected via surveys from employees across multiple industries. The study emphasizes the identification of least indicators in three cyberloafing catego-ries: browsing-related activities, non-work-related email usage, and interacting behaviors, as well as in two OCB dimensions: or-ganizational (OCBO) and personal (OCBP). Statistical analyses were conducted to explore correlations between these behaviors and performance metrics.Findings reveal a nuanced relationship: while certain cyberloaf-ing behaviors detract from productivity, others have negligible or even positive impacts under specific conditions. Strong OCB, how-ever, consistently correlates with higher performance levels. These insights underline the importance of a balanced evaluation of em-ployee behavior.This research provides a novel framework for organizations to assess employee productivity comprehensively, accounting for both adverse and beneficial behaviors. The resulting EPET offers a practical tool to enhance organizational performance evaluation and decision-making processes.